2012
DOI: 10.1038/ki.2011.412
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic recruitment of regulatory T cells as a therapy for ischemic acute kidney injury

Abstract: Regulatory T cells (Tregs) are key components of the peripheral tolerance system and have become an immunotherapeutic agent for treating inflammatory processes. This therapeutic option, however, is hampered by problems arising from isolating and expanding desirable Tregs. Here we used an alternative approach with a pharmacologic agent to stimulate Tregs to achieve immunosuppressive effects. Pretreatment of mice with the naturally occurring sphingosine N, N-dimethylsphingosine (DMS) was found to increases both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 43 publications
(64 reference statements)
1
56
0
Order By: Relevance
“…If given 10 minutes before ischemia, DMS protected against IRI, an effect that was negated by prior PC61 treatment to deplete Tregs. 41 DMS is a sphingosine kinase inhibitor; however, another more specific sphingosine kinase inhibitor did not produce similar results, suggesting that the mechanism is an unknown off-target effect. 41 Sphingosine-1-phosphate analog (FTY720) enhanced Treg numbers in the spleen and kidney and protected mice from kidney IRI.…”
Section: Targeting Of Intrinsic Tregsmentioning
confidence: 83%
See 2 more Smart Citations
“…If given 10 minutes before ischemia, DMS protected against IRI, an effect that was negated by prior PC61 treatment to deplete Tregs. 41 DMS is a sphingosine kinase inhibitor; however, another more specific sphingosine kinase inhibitor did not produce similar results, suggesting that the mechanism is an unknown off-target effect. 41 Sphingosine-1-phosphate analog (FTY720) enhanced Treg numbers in the spleen and kidney and protected mice from kidney IRI.…”
Section: Targeting Of Intrinsic Tregsmentioning
confidence: 83%
“…40 Several recent preclinical studies suggest that other pharmaceutical agents target intrinsic Tregs and may be beneficial in AKI. Lai et al 41 observed rapid and transient trafficking of Tregs into the kidney on administration of dimethylsphingosine (DMS) in mice. If given 10 minutes before ischemia, DMS protected against IRI, an effect that was negated by prior PC61 treatment to deplete Tregs.…”
Section: Targeting Of Intrinsic Tregsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Whether adoptively transferred Tregs must localize in the kidney to provide protection from IRI is unknown. This study does not provide any information on the site(s) of action for adoptively transferred Tregs; this is currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there are reports that Treg activation protects against experimental ischemia-reperfusion injury in other organs, such as the liver 38 and kidney. 39 Most of these studies do not address the exact mode of Treg activation and interaction with innate immune cells, though these phenomena are generally associated with increased Treg levels in the injured organ.…”
Section: Significance Of T-regulatory Cells In Ischemiareperfusionmentioning
confidence: 99%